ACL injury risk in elite female youth soccer: Changes in neuromuscular control of the knee following soccer-specific fatigue - De Ste Croix, M. B. A.; Priestley, A. M.; Lloyd, R. S.; Oliver, L. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Fatigue is known to influence dynamic knee joint stability from a neuromuscular perspective, and electromechanical delay (EMD) plays an important role as the feedback activation mechanism that stabilizes the joint. The aim of this study was to investigate the influence of soccer-specific fatigue on EMD in U13-, U15-, and U17-year-old female soccer players. Thirty-six youth soccer players performed eccentric actions of the hamstrings in a prone position at 60, 120, and 180°/s before and after a soccer-specific fatigue trial. Surface electromyography was used to determine EMD from the semitendinosus, biceps femoris and gastrocnemius. A time × age × muscle × velocity repeated measures analysis of variance was used to explore the influence of fatigue on EMD. A significant main effect for time (P = 0.001) indicated that EMD was significantly longer post- compared with pre-fatigue (58.4% increase). A significant time × group interaction effect (P = 0.046) indicated EMD was significantly longer in the U13 age group compared with the U15 (P = 0.011) and U17 (P = 0.021) groups and greater post-fatigue. Soccer-specific fatigue compromised neuromuscular feedback mechanisms and the age-related effects may represent a more compliant muscle-tendon system in younger compared with older girls, increasing risk of injury.